Breeding notes on some Padang-Sugihan birds - Nash, Anne D; Nash, Stephen V (KUKILA, 1985)
Summarized herein are various breeding and nesting observations on 34 species of lowland birds, compiled between September 1984 and August 1985, In the Padang - Sugihan Wildlife Reserve, South Sumatra. The reserve, with an area of 75,000 ha, lies approximately 45 km north-east of Palembang. The habitat types of the reserve are described in the checklist elsewhere in this issue.